Epigenetic Biomarkers in Cardiovascular Diseases - Soler-Botija, Carolina; Gálvez-Montón, Carolina; Bayés-Genís, Antoni (Frontiers in Genetics, 2019)
ABSTRACT Cardiovascular diseases are the number one cause of death worldwide and have a great impact on quality of life and medical costs. Enormous efforts are being made in research to obtain new tools for an efficient and quick diagnosis and prognosis of these diseases. Discoveries in epigenetic mechanism have related several pathologies, including cardiovascular diseases, with epigenetic dysregulation. This have implications on disease progression and opens new preventive strategies. Advances in methodology and big data analysis have identified novel mechanisms and targets involved in numerous diseases, making possible a more individualize epigenetic maps that would lead to a personalized diagnosis and treatment. This pave the way to what is called pharmacoepigenetics, which consider differences in epigenetic basis of each patient to predict drug response and develop a tailored therapy. Likewise, epigenetic biomarkers have emerged as a promising instrument for a consistent diagnosis and prognosis of cardiovascular disease. Their good accessibility and feasible methodology of detection make them suitable for implantation in clinical practice. However, it is a major requirement to perform multicenter studies with a large sample population to determine confidently which epigenetic biomarkers are reliable to be implanted in clinical routine. This review, therefore, focuses on epigenetic therapies in cardiovascular diseases, current discoveries and controversy in epigenetic biomarkers aimed to improve the diagnosis, disease prognosis and therapy in cardiovascular patients.